(3bUjOI aj eOM eMj GdOjf GHf YQHjs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj , (B1143 (3g`s
(3ChdgG (B:s
(3NPG MjK gHJ fSeI GdHGf hGdQfO (B*** (3hYQLG Ydi Jdc GdeYGde ef fLO , hHKG ZQGeG jG Ndjdj cdeG (B*** (3WaJg OehY GdYjf jROGO aj GdhJOs
(3BNQgG (B:s
(3hdG RGd QVhGf ef Gddg OGFeG (B*** (3Ydi gjcd GdCfhGQ aj Pdc GddMO , eOi GdOgQ eG fGM GdMeGe eZQOG (B*** (3agjL ef Cgd Gdghi dhYI GdhLOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 32s
(3eYLe GdeDdajf(B: 2 / 176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs